1998
DOI: 10.1002/jlb.64.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of urokinase on monocytes and in serum of children with AIDS; effects on lymphocyte activation and surface marker expression

Abstract: Urokinase (UK) type plasminogen activator is a serine protease produced by activated human monocytes. Despite the well-documented roles played by UK in cell-mediated immunity in healthy humans, the roles played by UK in the derangements of cell-mediated immune responses observed in HIV disease remain largely undefined. In these studies the numbers of peripheral blood lymphocytes and monocytes bearing surface UK (UK ؉ ) as well as serum levels of UK (flow microfluorimetry and ELISA, respectively) were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In healthy adults, the circulating concentration of suPAR is often between 1 and 2 ng/mL, depending on the sample material, the anticoagulant, and the assay used [27,52]. The reference concentration for suPAR in children is unknown, but the serum concentration of uPA is comparable in children and adults [53,54]. Although the median plasma concentration of suPAR was 12 ng/mL in the healthy children, such concentrations have previously been demonstrated in healthy adults [27].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adults, the circulating concentration of suPAR is often between 1 and 2 ng/mL, depending on the sample material, the anticoagulant, and the assay used [27,52]. The reference concentration for suPAR in children is unknown, but the serum concentration of uPA is comparable in children and adults [53,54]. Although the median plasma concentration of suPAR was 12 ng/mL in the healthy children, such concentrations have previously been demonstrated in healthy adults [27].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, uPA-uPAR has been shown to process CCL14 into an active form (54) and to modulate the chemotactic effect of CCL11 (55). In addition, uPA has been shown to increase the number of CD4 ϩ and CD8 ϩ T cells from healthy children in vitro (56), whereas uPA-deficient mice showed a reduced infiltration of CD4 ϩ ͞CD11b ϩ ͞CD18 ϩ cells in their lung and had an increased mortality by infection of Criptococcus neoformans (57). In vitro, HIV infection of cell lines, PBMC, and͞or MDM has resulted in increased expression of uPAR (13) as well as of certain CC chemokines such as CCL2 (58), CCL3, and CCL4 (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we have recently shown that high serum levels of suPAR are a major negative prognostic factor in HIV infection independently of the clinical stage, viremia levels, and CD4 ϩ T cell counts (11). In addition, dysregulation of the uPA-uPAR system has been observed in children with AIDS in terms of a decreased number of uPA ϩ circulating monocytes (56) and, more recently, in granulocytes of HIV-infected individuals, where the levels of uPAR expression reflected the number of peripheral blood CD4 ϩ T lymphocytes (14).…”
Section: Discussionmentioning
confidence: 99%
“…HIV‐1 infection is characterized by profound and inappropriate immune activation [22, 23], which may in part explain the perturbations in the uPA‐uPAR system associated with HIV‐1 infection. Thus, HIV‐1‐infected patients have high circulating levels of suPAR [1] and uPA [24], and the uPAR expression is reduced on granulocytes [25] but increased on activated T cells [4]. Furthermore, HIV‐1 infection of T and monocytic cell lines increases uPAR expression on both an mRNA and protein level [26, 27].…”
Section: Introductionmentioning
confidence: 99%